Perubahan Makna Kata Serapan dalam Surat Kabar Asy-Syarqu Al-Ausath Vol. 47: Kajian Semantik - Saladin, Cundarojat Sidiq; Akmaliyah, Akmaliyah; Rohanda, Rohanda (Aksara: Jurnal Bahasa dan Sastra, 2025)
The development of science, technology and culture cause the meaning of a word to change. Word absorption in foreign language also develops over time. This research aims to analyze how the meaning of the word has changed compared to its original meaning in the newspaper Asy-Syarqu Al-Ausath edition Vol. 47. Understanding the changes in the meanings of absorbing words helps prevent ambiguity and supports communication accuracy in the Arabic world. It belongs to descriptive qualitative research. The approach applied in this research is the change of meaning according to Sarwiji Suwandi's view. The data collection technique used listening method followed by documentation technique. Data analysis in this study used intralingual pairing method with the technique of connecting-comparing (HBB). The results of this study show that there are two types of meaning changes, namely (1) generalization or expansion of meaning, for example in the absorption word al-barliman (البرلمان) and (2) specialization or narrowing of meaning as in the absorption word diplomasiyah (الدبلوماسية). Of the two types of meaning changes in the Vol. 47 edition of Asy-Syarqu Al-Ausath newspaper, specialization or narrowing changes in meaning are most often found. So it can be seen that English words absorbed into Arabic tend to experience a process of specialization or narrowing of meaning.Keywords: Loanwords, Change of Meaning, Semantic, Arabic Newspaper